Features of the Imam Abu Hanifa Methodology (Journal of Philosophy Culture and Political Science, 2019)
Article considers the theological views of Imam Abu Hanifa in various areas of Islamic law, in order to identify the basic principles and provisions that build the basic methodological basis of the Hanafi School. Hanafi School became widespread in the Muslim world and its followers are the majority of Muslims that are living in Kazakhstan and the CIS countries, such us: Russia, Uzbekistan, Tajikistan, Kyrgyzstan, Volga region, in the Urals, Siberia and in Crimea, partly in the North Caucasus and Azerbaijan. Religious and legal heritage of Abu Hanifa and his students is still relevant today. Rationality is the methodological particularity of the Hanafi School theologians. In combination with legal installations and taking into account local traditions, it practically had no disagreements and became the property of the global legal culture. Hanafism was able to not only unite the cultural and legal monuments of Central Asia and Kazakhstan, but also universalize their centuries-old experience based on the transformation of classical Islamic legal signs. Analyzing Abu Hanifa’s methodology in theological sciences, can be traced the tradition of features’ transmitting in the further works of the Hanafi School theologian scholars of the of the Maverannahr school of Fiqh. The aim of the author was to study and identify the basic principles and rules for the application of the tools of law by Imam Abu Hanifa, as well as his students in various areas of Islamic law.Key words: inheritance law, Fiqh, Islam, Hanafi School, history, Islamic law.